Análise de carga em Robo Kuka KR60 para linha de prensa robotizada - Soares, Claudio (2014)
This field research with a case study want to analyze the work strain in a robot, used to transfer automotive parts from a stamping press line to the end of line conveyor. This equipment has presented a higher mechanical fault frequency than other robots used in the same process, even working with a lower static load compared to others. The project result intends to identify the critical point in the process and the failure root cause.